Intercellular pectic protuberances in Hymenaea stigonocarpa (Fabaceae, Caesalpinioideae): Occurrence and functional aspects - Sousa Paiva, Elder Antonio; Machado, Silvia Rodrigues [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2008)
A study of the anatomy and ultrastructural aspects of leaf mesophyll and floral nectaries of Hymenaea stigonocarpa Mart. ex Hayne revealed the presence of intercellular pectic protuberances (IPPs) linking adjacent cells in both the leaf palisade cells and the secretory parenchyma of the floral nectary. Samples of the middle third of the leaf blade and of floral nectaries in anthesis were collected, fixed, and processed using standard procedures for light, transmission, and scanning electron microscopies. The IPPs of palisade cells of the mesophyll and the secretory parenchyma cells of the floral nectary take the form of scalae or strands, respectively. No evidence of the specific synthesis of these structures was observed, and they are apparently formed by the separation of adjacent cells due to cell expansion, when intercellular spaces develop. The IPPs observed in H. stigonocarpa increase cellular contact and probably act in apoplastic transport.
Keywords: apoplast; cell communication; intercellular pectic protuberances; intercellular transport; middle lamellae; pectin